KEPUASAN MAHASISWA MAGISTER MANAJEMEN TERHADAP PEMBELAJARAN BERDASARKAN EVALUASI KINERJA DOSEN DENGAN PENILAIAN BERDASARKAN PERSEPSI MAHASISWA PADA ITBHAS BUKITTINGGI - Suryanto, Dasep Suryanto; Adevi, Isye Rahayu; Adriansyah, Adriansyah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The performance of lecturers by students is the most important thing in measuring student satisfaction in learning carried out by lecturers. This assessment functions as a form of supervision of lecturers' performance in implementing the Tridharma of Higher Education. This assessment aims to evaluate lecturer performance towards student satisfaction in the Master of Management study program in the learning carried out. The research method uses Multiple Linear Regression with data processing techniques using SPSS Clementine version 12.0. From the research results, it is known that overall or together it does not affect student satisfaction in the learning process. However, if we look at the percentage of influence together, it is only 11.4%. Meanwhile, for partial influence, the influence that is the most important reference in influencing student satisfaction is the lecturer's ability to manage the class, as evidenced by the sig value of 0.000.Keywords: Evaluation, Lecturer Performance, Student Satisfaction